Enhancer-driven Shh signaling promotes glia-to-mesenchyme transition during bone repair - Xin Shen; Hang Zhang; Zesheng Song; Yangjiele Dong; Xiao Ge; Shenghao Jin; Songsong Guo; Ping Zhang; Yu Fu; Yuchi Zhu; Na Xiao; Dongmiao Wang; et al. (Bone Research)
Abstract Plp1-lineage Schwann cells (SCs) of peripheral nerve play a critical role in vascular remodeling and osteogenic differentiation during the early stage of bone healing, and the abnormal plasticity of SCs would jeopardize the bone regeneration. However, how Plp1-lineage cells respond to injury and initiate the vascularized osteogenesis remains incompletely understood. Here, by employing single-cell transcriptional profiling combined with lineage-specific tracing models, we uncover that Plp1-lineage cells undergoing injury-induced glia-to-MSCs transition contributed to osteogenesis and revascularization in the initial stage of bone injury. Importantly, our data demonstrated that the Sonic hedgehog (Shh) signaling was responsible for the transition process initiation, which was strongly activated by c-Jun/SIRT6/BAF170 complex-driven Shh enhancers. Collectively, these findings depict an injury-specific niche signal-mediated Plp1-lineage cells transition towards Gli1+ MSCs and may be instructive for approaches to promote bone regeneration during aging or other bone diseases.